Experience with rituximab in refractory idiopathic inflammatory myopathy - García-Salazar, Elmer R. (2013)
Clinical and laboratory characteristics of two patients who received rituximab for refractory idiopathic inflammatory myopathy (IIM) are described. Patients were refractory to conventional treatment with disease-modifying antirheumatic drugs (DMARDs) so they received rituximab 1 g dose every 14 days in two biannual cycle infusions. Data of proximal muscle strength, pathognomonic skin lesions, CPK, SGOT, LDH and ESR, results of electromyography, muscle and skin biopsy were obtained from the medical records. None of the cases presented drug reaction or infections during and following infusions. Rituximab showed effectiveness in clinical and enzymatic response in patients with dermatomyositis refractory to corticosteroids and traditional DMARDs.